Improving Floodplain Management: Implications for Salmon, Public Safety, and Global Warming - Siemann, Dan; Kirkpatrick, DeeAnn (University of Washington Water Center, 2010)
Current floodplain management policies in Puget Sound have led to significant development in floodplains, loss of aquatic and riparian habitat, and diminished floodplain function. The consequences include costly floods, declines of salmon and orca populations, and heightened risk to public safety. Climate change is likely to make these problems worse. A recent Biological Opinion details floodplain management problems in Puget Sound and the role that the National Flood Insurance Program plays in influencing development decisions. DeeAnn Kirkpatrick from NMFS, who wrote the Biological Opinion, and Dan Siemann of the National Wildlife Federation, which filed the lawsuit that led to the Biological Opinion, will co-present.
Keywords: floodplains; riparian areas; habitat conservation; natural resource management; floods; salmon; Salmonidae; whales; Cetacea; habitat destruction; public safety; global warming